Analysis of the Chemotherapy-Free Interval following Image-Guided Ablation in Sarcoma Patients. (15th February 2020) - Sutton, Charles; Zhang, Yachao; Kim, DaeHee; Yarmohammadi, Hooman; Ziv, Etay; Boas, Franz E.; Sofocleous, Constantinos T.; Tap, William D.; D'Angelo, Sandra P.; Erinjeri, Joseph P.
Abstract : One way to enhance quality of life for patients with metastatic sarcoma is to maximize time off chemotherapy—a chemotherapy-free interval. While image-guided ablation of sarcoma metastases may reduce the need for chemotherapy, it remains unknown how long ablation could extend the chemotherapy-free interval. The purpose of our study was to determine the chemotherapy-free interval in comparison to overall survival and progression-free survival in sarcoma patients who undergo ablation procedures. An IRB-approved, single institution, HIPAA compliant database was queried for sarcoma patients who underwent image-guided ablation procedures between 2007 and 2018. Patient demographics, histologic subtype, and other clinical characteristics were recorded. Kaplan-Meier analysis was performed to compute median overall survival, median progression-free survival (local and distant), and the median chemotherapy-free interval (systemic and cytotoxic) after ablation. Univariate and multivariate analyses were performed using the log-rank test and Cox proportional-hazards model, respectively. A total of 100 sarcoma patients were included in the analysis. The most common histologic subtype was leiomyosarcoma (38%). Median overall survival after ablation of sarcoma metastases was 52.4 months (95% CI: 46.9–64.0 months). The median systemic chemotherapy-free interval following ablation of sarcoma metastases was 14.7 months (95% CI: 8.6–34.3 months). The median cytotoxic chemotherapy-free interval following ablation of sarcoma metastases was 81.3 months (95% CI: 34.3-median not reached). In conclusion, ablation of sarcoma metastases can provide an extended systemic chemotherapy-free interval of greater than 1 year. Ablation of sarcoma metastases may improve patient quality of life by extending the chemotherapy-free interval.